Did the UN convention on the rights of the child reduce child mortality around the world? An interrupted time series analysis - Tait, Christopher A. (BMC Public Health, 2020)
BACKGROUND: Child mortality has been reduced by more than 50 % over the past 30 years. A range of secular economic and social developments have been considered to explain this phenomenon. In this paper, we examine the association between ratification of the Convention on the Rights of the Child (CRC), which was specifically put in place to ensure the well-being of children, and declines in child mortality. METHODS: Data come from three sources: the United Nations Treaty Series Database, the World Bank World Development Indicators database and, the Polity IV database. Because CRC was widely ratified, leaving few control cases, we used interrupted times series analyses, which uses the trend in the health outcome before policy exposure to mathematically determine what the trend in the health outcome would have been after the policy exposure, if it had continued ‘as is’ – meaning, if the policy exposure had not occurred. RESULTS: CRC ratification was associated with declining child mortality. CRC ratification was associated with a significant change in shorter-term child mortality trends in all groups except high-income, non-democratic countries and low-imcome democratic countries. CRC ratification was associated with long-term child mortality trends in all groups except middle-income, non-democratic countries. CONCLUSIONS: Child mortality rates would likely have declined even in the absence of CRC ratification, but CRC is associated with a larger decline. Our findings provide a way to assess the effects of widely-held societal norms on health and demonstrate the moderating effects of democracy and income level.